2019
DOI: 10.1161/atvbaha.119.312589
|View full text |Cite
|
Sign up to set email alerts
|

IDOL G51S Variant Is Associated With High Blood Cholesterol and Increases Low-Density Lipoprotein Receptor Degradation

Abstract: Objective: A high level of LDL-C (low-density lipoprotein cholesterol) is a major risk factor for cardiovascular disease. The E3 ubiquitin ligase named IDOL (inducible degrader of the LDLR [LDL receptor]; also known as MYLIP [myosin regulatory light chain interacting protein]) mediates degradation of LDLR through ubiquitinating its C-terminal tail. But the expression profile of IDOL differs greatly in the livers of mice and humans. Whether IDOL is able to regulate LDL-C levels in humans remains to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Studies in non-human primates show that gain or loss of IDOL function leads to a corresponding increase and reduction in plasma LDL levels, respectively ( 4 ). In addition to experimental data, genetic studies have provided further evidence to support the notion that IDOL may potentially be involved in LDL metabolism ( 5 , 6 , 7 ). A recent study in children with untreated familial hypercholesterolemia (FH) has shown that plasma concentration of IDOL was elevated and was significantly associated with total and LDL cholesterol levels ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in non-human primates show that gain or loss of IDOL function leads to a corresponding increase and reduction in plasma LDL levels, respectively ( 4 ). In addition to experimental data, genetic studies have provided further evidence to support the notion that IDOL may potentially be involved in LDL metabolism ( 5 , 6 , 7 ). A recent study in children with untreated familial hypercholesterolemia (FH) has shown that plasma concentration of IDOL was elevated and was significantly associated with total and LDL cholesterol levels ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between plasma lipid profiles and the IDOL gene polymorphisms was poor, and previous studies showed inconsistent results. Adi et al [ 24 ] reported that the rs149696224 SNP in the IDOL gene was related to the high LDL-C levels in the Chinese Uygur population. Their study showed the G51S mutation stabilizes IDOL protein through inhibiting its dimerization and self-ubiquitination and, consequently, leading to increased LDLR degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin regulatory light chain interacting protein (MYLIP, also named IDOL) is an important ubiquitin E3 ligase, which mediates low density lipoprotein receptor (LDLR) degradation through ubiquitination reaction and affect blood lipid levels [50]. Previous reports indicated the LDLR-related protein (LRP1B) was discovered as a putative tumor suppressor and frequently inactivated in lung cancer cells [51,52].…”
Section: Discussionmentioning
confidence: 99%